Staff members working in the Alumni Publicity Office, November 6, 1934 - Munro, Melville S. (Tufts Archival Research Center, 2005)
8x10; Munro Scrapbook: Vol. 40, Box No. 59, Pg. 52; (left to right): Geraldine E. Minton, L. Helen Erb, Alicia R. Breen, Joseph W. Morton, Joan Franceschini